Automated Smoke and Gas Leakage Detector with IoT Monitoring System in Rural Area - Rosli, Amirrul Afiq; Abdullah, Mohammad Faiz Liew (Evolution in Electrical and Electronic Engineering, 2022)
The majority of explosions are triggered by gas leakage that goes unnoticed in the pre-detection stage. A gas leak resulted in a tragic accident because it has optimal properties such as high heat value, less smoke, less soot, and less environmental impact, liquefied petroleum gas (LPG) or propane. The objective of this project study is to design a tool using technology and the internet of things (IoT) that functionally detects and prevents wireless threats. A device made from microcontroller Arduino UNO that controls all activity of the device alongside node WiFi module, nodemcu ESP8266 that connected and communicated using the internet to send a notification warning to users. The device's efficiency is examined in this study by running multiple trials to see how well the sensor responds to gas or smoke leaks. The system displayed a success rate of 25 out of the total of 30 repeated measurements, giving the device efficiency of 83 percent. This project demonstrates that it is able to detect and monitor gas leaks in a reasonably enclosed space. The module may be used as a household application to monitor and take appropriate control actions in various conditions.